Analisis dan Pengembangan Sistem Penerimaan Siswa Baru Tingkat SMA Berbasis Web dengan Metode Kualitatif - Meily Fristia Sinaga; Sri Pita Locha Br Surbakti; Tegar Meskur Fetaroma Zalukhu; Muhammad Diarmansyah Batubara (Jurnal Syntax Transformation, 2021)
Currently many schools, especially at the high school level, have not maximized the advancement of information technology specifically in the admission of new students to still use conventional or manual. Therefore the need for information technology is very important for schools in getting things done quickly and easily and obtaining information effectively. This research was conducted to analyze and develop an online web-based application that is able to manage the implementation of New Student Admissions specifically at Free Methodist 2 Medan High School, namely registration, selection, and announcement. The data collection techniques in this study are Observation and Interview. The method used is qualitative method. Testing is done by means of black-box testing and the analytical technique used in this study is descriptive analysis. The Web uses PHP and SQL programming languages. In this system the author develops a new system and adds registration pathways namely zoning, achievement, teacher or transfer child pathways, and affirmations. The system is expected to have an impact on school accreditation and the increase of qualified new students. Based on this, the results of the proposed system design of the author can overcome the shortcomings of the system running in Private Free Methodist High School 2 Medan. Testing of the author's proposed system can run smoothly and in line with expectations. The implementation of the system i.e. the proposed PSB of the author can be accepted and understood by the parties involved in writing.